THE MACEDONIAN LANGUAGE IN THE CONTEXT OF SLAVIC CULTURE (Philological Studies, 2025)
The Macedonian language, through its centuries-old tradition, is directly connected with the development of Slavic culture. Their mutuality is seen from the fact, confirmed in Slavic science, that the Old Slavonic language is based on the South Macedonian speech, from the vicinity of Thessaloniki, more precisely from the Macedonian speeches from the villages of Suho, Visoka and Zarova in Aegean Macedonia. In the 19th century, more precisely in 1896, the Slovenian Slavist Vatroslav Oblak, studying the Macedonian language in the field, put forward the Macedonian theory for the origin of the Old Slavonic language. Therefore, the role of the Macedonian language in the context of Slavic culture and communication is significant. The idea for the spiritual, cultural and economic unification of the Slavic peoples, appeared in the 9th century, with the Moravian mission of the Pan-Slavic brothers Saints Cyril and Methodius. The idea was revived again in the late 18th and early 19th centuries, a period when the Slavic peoples were under the onslaught of Germanization, Hungarianization, and Hellenization. This was the period when Slavic studies were established as a science, when intensive cooperation between Slavists began, all to preserve the autochthonous Slavic culture. The Macedonian cultural revival had begun with a fight against Hellenization, through the efforts for restoration of the Ohrid Archbishopric and the return of the Old Church Slavonic language in church services instead of the forcibly introduced Greek language, as well as the opening of schools in the vernacular. Due to the assimilationist policies towards the Macedonian people in the 19th century and the division of Macedonia in 1913 with the Bucharest Treaty, the codification of the Macedonian language finally took place in 1945.
Keywords: Macedonian, Old Slavonic, language, Slavic, culture